2011
DOI: 10.1590/s0004-27302011000800020
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cutoff points for body mass index, waist circumference and HOMA-IR to identify a cluster of cardiometabolic abnormalities in normal glucose-tolerant Brazilian children and adolescents

Abstract: OBJECTIVE: The aim of this study was to establish the best cutoff values for waist circumference (WC), body mass index (BMI) and HOMA-IR (HR) to identify a cluster (> 3) of cardiovascular risk factors (CVRF) in normal glucose-tolerant (NGT) Brazilian children and adolescents. SUBJECTS AND METHODS: Cross-sectional study of 319 individuals (aged 10 to 19y) from a southern Brazilian city. Gender-specific receiver-operating characteristics (ROC) curves were constructed to assess cutoffs values of BMI (kg/m², WC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…Six studies,18 , 20 - 23 were carried out in foreign countries between 2005 and 2015 and one19 was performed with Brazilian adolescents in 2011. The smallest sample consisted of 57 participants23 and the largest had 3203 22.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies,18 , 20 - 23 were carried out in foreign countries between 2005 and 2015 and one19 was performed with Brazilian adolescents in 2011. The smallest sample consisted of 57 participants23 and the largest had 3203 22.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies associated WC with CVRF and metabolic syndrome in Brazilian children, and specific WC values could predict several cardiometabolic risks 7,47,48 . Rocco et al 48 suggested WC cutoff values to detect a cluster of CVRF (WC = 80.5 cm for boys; WC= 83.0 cm for girls) in Brazilian children and adolescents.…”
Section: Discussionmentioning
confidence: 97%
“…Rocco et al 48 suggested WC cutoff values to detect a cluster of CVRF (WC = 80.5 cm for boys; WC= 83.0 cm for girls) in Brazilian children and adolescents. Obesity in Brazilian children was associated with the duration of the breast-feeding period, the legal guardian's weight excess, sedentarism, physical activity level, and rapid chewing 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Em 2011, Rocco et al 24 publicaram um estudo com objetivo de estabelecer pontos de corte para PC, IMC e resistência à insulina para identificar fatores de risco concomitantes em crianças e adolescentes com tolerância normal trada para os valores críticos para risco de excesso de gordura abdominal, em nosso estudo, para meninos foi de 73,7 e para as meninas foi de 71,5 quando analisada a faixa etária de 10 a 18 anos.…”
Section: I S C U S S ã Ounclassified